Economical evaluation of a cogeneration system for a building complex - Adiguzel, Nesrin; Comakli, Omer; Ekmekci, Ismail; Pusat, Saban (SAGE PUBLICATIONS LTD, 2015)
In this study, the suitability of using cogeneration system for the Akturk Building Complex (located in Istanbul) was investigated using electricity and heat consumption data by considering five different cogeneration system capacities (800, 1200, 1400, 2000 and 2600kW). The different capacities were compared using data of the payback period of investment, amount of net savings, ratio of meeting demand and part- load efficiency of the cogeneration system. Although payback periods of the investment for different capacities are close to each other, 1200kW capacity cogeneration system is proved to be suitable for the Akturk Building Complex because it has the shortest payback period (1 year 5 months).
Keywords: Cogeneration; energy efficiency; economical evaluation; Istanbul; THERMOECONOMIC ANALYSES; ENGINE; ENERGY; EFFICIENCY; Thermodynamics; Engineering